PRODUÇÃO E QUALIDADE DE MELANCIA FERTIRRIGADA COM NITROGÊNIO E POTÁSSIO - Medeiros, Damiana Cleuma de (Universidade Federal Rural do Semi-Árido, 2008)
The state of the Rio Grande do Norte is the second greatest watermelon producer in the Brazilian Northeast. The mineral nutrition is one of the factors that affect directly yield and fruit quality of the watermelon crop, and nitrogen and potassium are the most required nutrients for this crop. For evaluating the effect of nitrogen and potassium doses, supplied through fertigation to the Mickylee watermelon crop, one experiment in 2005 and other in 2006 were conducted. The experiments were carried out in a 3 x 3 + 2 factorial scheme, in randomized complete blocks with three replications. The treatments were the combinations of three doses of nitrogen (50%, 100%, and 150% of standard dose 96.0 kg ha-1) and three doses of potassium (50%, 100%, and 150% of standard dose 153.0 kg ha-1) plus two additional treatments: 1) 100% nitrogen standard dose + 0% potassium and 2) 0% nitrogen + 100% potassium standard dose. These standard doses are the recommended ones for the crop. The evaluated traits were: total number of fruits (NTF), mean fruit mass (MF), total fruit yield (PTF), mean pulp firmness (FP), mean fruit pH (pH), mean total soluble solids (SST) and mean vitamin C content (VIT C). The maximum points obtained were: 143.34 kg ha-1 N and 179.87 kg ha-1 K for NTF; 96.64 kg ha-1 N and 185.54 kg ha-1 K for MF; 88.37 kg ha-1 N and 145.73 kg ha-1 K for PTF; 54.41 kg ha-1 N and 96.21 kg ha-1 K for FP; 110.83 kg ha-1 N and 152.88 kg ha-1 K for pH; 125.52 kg ha-1 N and 105.50 kg ha-1 K for SST; 120.60 kg ha-1 N and 173.90 kg ha-1 K for VIT C.
Production and quality of watermelon fertirrigated with nitrogen and potassium
Keywords: Citrullus lanatus; Mickylee; Yield; Fertigation; Citrullus lanatus; Mickylee; Produtividade; Fertirrigação; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA